Enhancing ESL writing using sentence variety checklist - Abdullah, Liza; Kassim, Rosnani; Abdul Ghani, Noor Amili; Ab. Rahman, Hazlinah; Md Zamin, Ainul Azmin (Human Resource Management Academic Research Society (HMARS), 2019)
Sentence variety is a fundamental aspect in writing to avoid stereotypes, thus making writing more interesting. However, ESL students are often found not using the different sentence structures in writing. Students seem to learn one basic pattern and stick to it. The reason could be due to lack of knowledge and practice to write a variety of sentence structures. They seem to be reluctant to learn more about it, and teachers are reluctant to teach. Despite being fundamental, little emphasis has been put on sentence variety in the ESL Writing classes because most of the time teachers and students think that as long as there are no grammatical errors, the writing is acceptable. Even with improvement, most of them may not really achieve encouraging results in writing. Hence, this study intended to examine the respondents’ writing performance before and after using a sentence variety checklist, and to analyse the respondents’ perceptions towards using the sentence variety checklist in their writing. Twenty university students from a pre-sessional English Language programme were selected to take part in this study and data were collected qualitatively from students’ essays and their responses from a 20-item survey questionnaire. The findings revealed a slight improvement in students’ writing. They also found the checklist made writing more interesting and made the students more aware of what they were writing. In conclusion, sentence variety checklist can be one of the tools for ESL students to boost students’ writing performance.